PENGARUH ENGLISH FOR SPECIFIC PURPOSES TERHADAP PERSIAPAN KERJA MAHASISWA DALAM PENINGKATAN ILMU PROMOSI KESEHATAN PADA MAHASISWA KESEHATAN MASYARAKAT INSTITUT KESEHATAN MEDISTRA LUBUK PAKAM - GINTING, SULASTRI BR; TINAMBUNAN, TEDTY ROHAYA (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2025)
English proficiency is an essential skill for public health students to meet global demands, particularly in health promotion, which requires cross-cultural communication and understanding of international literature. English for Specific Purposes (ESP) is considered a relevant learning method because it aligns instructional materials with students’ academic and professional needs. Through this approach, students can improve their English competence specific to the health field, thereby enhancing job readiness and health promotion competence. This study employed a quantitative survey approach to analyze the effect of ESP on public health students’ job readiness and knowledge in health promotion. The sample consisted of 50 students selected using a purposive sampling technique who had previously taken ESP courses. The independent variable was the ESP method, measured through indicators such as material relevance, technical health vocabulary, reading skills, report writing, and presentation abilities. The dependent variable was job readiness, indicated by communication ability, mastery of health promotion, and access to international literature. Data were analyzed using simple linear regression and Pearson correlation with SPSS version 28. The results showed a Pearson correlation coefficient of r = 0.732 with a p-value of 0.000 < 0.05, indicating a strong and significant positive relationship between ESP and students’ job readiness. The regression equation Y = 1.12 + 0.76X with an R² value of 0.536 indicates that the ESP method contributes 53.6% to improving job readiness and health promotion knowledge, while 46.4% is influenced by other factors. Thus, better ESP implementation significantly enhances students’ preparedness for careers in public health.